Nature of the active site in ziegler-natta olefin polymerization catalysis systems - a computational investigation - Kumawat, Jugal; Gupta, Virendra Kumar; Vanka, Kumar (European Journal of Inorganic Chemistry, 2014)
Pull quantum chemical calculations with density functional theory (DET) show that a principal role of donors in Ziegler-Nana (ZN) oh-din polymerization catalysts is to coordinate to the metal center at the active sites on the MgCl2 surface. Thereby, the behavior of the catalyst is modulated to favor insertion over termination and, thus, polymerization occurs. This is shown to be true for a range of different donors. The calculations indicate that active sites that feature anionic chloride ligands at the titanium center (the conventional model for the active site) would lead to lower-molecular-weight riolymers. If an -OC2H5 group were present instead of a chloride ligand, the active site would much more effectively produce long chain polymers. Therefore, the current work provides important new insights into the nature of the ZN polymerization process.
Keywords: Alkene polymerization; Density functional calculations; heterogeneous catalysis; Insertion; Polymers

One-pot synthesis of cyclic carbonates from aldehydes, sulfur ylide, and CO2 - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Synlett, 2014)
Treatment of aldehydes with sulfur ylide (CH2=SOMe2 or CH2=SMe2), in the presence of CO2 (1 atm) bubbled sequentially under mild conditions, produces cyclic carbonates in preparative yields. Sodium iodide formed in situ promotes the reaction between epoxide as intermediate and CO2 at ambient conditions, thus constituting a powerful metal-free synthesis of organic cyclic carbonates directly from aldehydes.
Keywords: Carbon dioxide; cyclic carbonates; cyclization; epoxides; Insertion

Transition-metal-catalyzed reactions involving arynes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Synthesis-Stuttgart, 2018)
The plethora of transformations attainable by the transition-metal-catalyzed reactions of arynes has found immense contemporary interest in the scientific community. This review highlights the scope and importance of transition-metal-catalyzed aryne reactions in the field of synthetic organic chemistry reported to date. It covers transformations achieved by the combination of arynes and various transition metals, which provide a facile access to a biaryl motif, fused polycyclic aromatic compounds, different novel carbocycles, various heterocycles, and complex natural products. 1 Introduction 2 Insertion of Arynes 3 Annulation of Arynes 4 Cycloaddition of Arynes 5 Multicomponent Reactions of Arynes 6 Miscellaneous Reactions of Arynes 7 Total Synthesis of Natural Products Using Arynes 8 Conclusion
Keywords: annulation; arynes; Cycloaddition; Insertion; multicomponent; Natural products; Transition Metal

Reactivity of four coordinate iridium complex towards hydrogen: an experimental and computational study - Agrawal, Nisha K.; Dash, Soumya R.; Vanka, Kumar; Nethaji, Munirathinam; Jagirdar, Balaji R. (Journal of Organometallic Chemistry, 2022)
Reaction of a four coordinate, 16-electron Ir complex, [Ir-(iPr)4(POCOP)(PPh3)] (4 ) (((iPr)4)(POCOP= 2,6-bis(di-isopropyl phosphinito)benzene, kappa(3)-C6H3-1,3-[OP((iPr))(2)](2)), with H-2 resulted in an oxidative addition product, cis-dihydride complex, cis-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( cis-5 ) presumably via the intermediacy of a sigma complex, [Ir(eta(2)-H-2)((iPr)4)(POCOP)(PPh3)]. The cis-dihydride complex completely isomerizes to the trans-dihydride complex trans-[Ir(H)(2) ((iPr)4)(POCOP)(PPh3)] ( trans-5 ) under ambient conditions in about 3 h. It was found that the steric and electronic features on the iridium center have significant influence on the approach of H-2 onto the metal center followed by oxidative addition and isomerization. The isomerization process was studied in detail and all the mechanistic aspects have been elucidated using a combination of both experimental work and computation. The cis-dihydride complex isomerizes to the trans-dihydride by compensating the trans influence of the strongly trans-directing hydride ligand. A mechanism involving the exchange of the position of PPh3 with a hydride ligand cis to itself via PPh3 dissociation and re-coordination thereby resulting in the formation of the trans-dihydride complex, has been proposed for the isomerization. The cis-dihydride was found to be a highly active catalyst for hydrogenation of ethy-lene. A competing reactivity study of cis-dihydride between isomerization versus insertion of C2H4 into the Ir-H bond, was studied experimentally and computationally. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: Hydrogenation; Insertion; iridium complex; isomerization; Oxidative addition; Reductive elimination

C=C insertion over N=C=O of allyl isocyanate into the Ge-Si bond of a germylene - Ajithkumar, V. S.; Khilari, Nripen; Ghanwat, Pratiksha B.; Koley, Debasis; Sen, Sakya S. (European Journal of Inorganic Chemistry, 2025)
Two isocyanates are reacted with the germylene, PhC(NtBu)(2)Ge-Si(SiMe3)(3) (1). Phenyl isocyanate undergoes catalytic cyclotrimerization with 1 leading to 1,3,5-triphenyl isocyanurate (2), while allyl isocyanate undergoes both cyclotrimerization and the C=C bond insertion between the Ge-Si bond. The constitution of 3 is determined by single-crystal X-ray studies. The contrasting reactivity pattern is explained by comprehensive density functional theory studies.
Keywords: Cyclotrimerization; Density functional theory; Germylene; Insertion; isocyanates